That Greece Might Still Be Free The Philhellenes in the War of Independence - St Clair, William (Open Book Publishers, 2008)
When in 1821, the Greeks rose in violent revolution against the rule of the Ottoman Turks, waves of sympathy spread across Western Europe and the United States. More than a thousand volunteers set out to fight for the cause. The Philhellenes, whether they set out to recreate the Athens of Pericles, start a new crusade, or make money out of a war, all felt that Greece had unique claim on the sympathy of the world. As Lord Byron wrote, "I dreamed that Greece might still be Free"; and he died at Missolonghi trying to translate that dream into reality. William St Clair's meticulously researched and highly readable account of their aspirations and experiences was hailed as definitive when it was first published. Long out of print, it remains the standard account of the Philhellenic movement and essential reading for any students of the Greek War of Independence, Byron, and European Romanticism. Its relevance to more modern ethnic and religious conflicts is becoming increasingly appreciated by scholars worldwide. This revised edition includes a new introduction by Roderick Beaton, an updated bibliography and many new illustrations.